The Effect of Case Reflection Discussions (DRK) on Improving Nursing Care Documentation According to 3S Standards (SDKI, SLKI, SIKI): a literature review - Andina Desiani Ekawaty; Blacius Dedi (Syntax Corporation Indonesia, 2024)
Nursing documentation is a means of communication between medical personnel aimed at restoring patient health. Documentation is nursing work that can facilitate nursing management, improve continuity of care, coordinate care, and evaluate patient interventions. DThe completeness and suitability of nursing care documentation in accordance with the 3S nursing care process standards (SDKI, SLIKI, SIKI) in several hospitals is still low. Implementing case reflection discussions can help improve a nurse's ability to carry out good and effective planning in improving the quality of nursing. This research is to determine the influence of case reflection discussions (drk) on improving nursing care documentation according to 3s standards (SDKI, SLKI, SIKI). This article was written using a literature study method which was analyzed from several journals related to the topic taken, journals were searched through Proquest, Pubmed, Google Scholar, Garuda, Sinta, which were then selected according to the topic, literature searches were carried out within the publication period journal from 2018 to 2024. The results of the discussion of the analysis of 20 literature reviews with hypothesis testing for each journal show that there is an influence of DRK on the quality of nursing care. DRK has the benefits of increasing knowledge, solving service problems, increasing awareness of quality practices and critical thinking. Nurses' knowledge influences the documentation of nursing care according to 3S standards (SDKI, SLKI, SIKI). One way to increase nurses' knowledge is with Case Reflection Discussions (DRK).